Textiles and clothing : environmental concerns and solutions - Shabbir, Mohd (Chemist) (John Wiley & Sons, Inc. ; Scrivener Publishing, LLC, 2019)
"All environmental aspects relating to the textile and clothing industry are discussed in this book."